Good Habits for Great Coding Improving Programming Skills with Examples in Python - Stueben, Michael (Apress, 2018)
Improve your coding skills and learn how to write readable code. Rather than teach basic programming, this book presumes that readers understand the fundamentals, and offers time-honed best practices for style, design, documenting, testing, refactoring, and more. Taking an informal, conversational tone, author Michael Stueben offers programming stories, anecdotes, observations, advice, tricks, examples, and challenges based on his 38 years experience writing code and teaching programming classes. Trying to teach style to beginners is notoriously difficult and can easily appear pedantic. Instead, this book offers solutions and many examples to back up his ideas. Good Habits for Great Coding distills Stueben's three decades of analyzing his own mistakes, analyzing student mistakes, searching for problems that teach lessons, and searching for simple examples to illustrate complex ideas. Having found that most learn by trying out challenging problems, and reflecting on them, each chapter includes quizzes and problems in each chapter. The final chapter introduces dynamic programming to reduce complex problems to subcases, and illustrates many concepts discussed in the book. Code samples are provided in Python and designed to be understandable by readers familiar with any modern programming language. At the end of this book, you will have acquired a lifetime of good coding advice; the lessons the author wishes he had learned when he was a novice.